Pre-Gratian medieval canonical collections: texts, manuscripts, concepts - Szuromi, Szabolcs Anzelm (Aus Religion und Recht, 2014)
Appendix I Firenze, Bibliotheca Medicea-Laurentiana, Ashburnham 53Appendix II St. Petersburg, Nationalnaya Biblioteka O. v. II. 4; Appendix III Writings of Gregory the Great (590-604) in the First Part of the 'Collectio Tripartita' (Comparative Table ofGregory the Great's Original Texts); Bibliography; Index of Manuscripts.